(untitled) (Journal of the College of Basic Education, 2022)
The study area is one of the agricultural areas, which is characterized by fertile soils and the abundance and diversity of vegetation were (the second improved vegetation index (EV12), the relative vegetation index (RVI), the soil-modified plant index (SAVI), and the vegetation cover index (NDVI), so the plant indicators and their study give excellent results. It is a strong indicator of environmental degradation and desertification, and a specific objective of the research stems from the evaluation of the spectral plant indicators used in the study, and the identification of the best ones in extracting the values ​​of vegetation cover in terms of their accuracy and ease of calculation to reach the most appropriate indicator for application. Indicators are considered one of the most accurate and best means of monitoring vegetation cover, based on remote sensing and geographic information systems. The study area was identified as (Al-Suwaira District), which belongs to Wasit Governorate. Which were taken in July 2007 and July 2018, the values ​​of four indicators were extracted, namely, the second improved vegetation index (EV12), the relative vegetation index (RVI), the soil modified vegetation index (SAVI), and the vegetation coverage index (NDVI). The research confirmed the determination of the places of density in the vegetation cover, which can be used in subsequent studies to determine the quality of the plant more accuratel. Using remote sensing technology to monitor and detect changes in vegetation cover, especially in agricultural areas, which are witnessing deterioration in their lands and a decline in productive areas.